Wildfire Smoke Cools Summer River and Stream Water Temperatures - David, Aaron T.; Asarian, J. Eli; Lake, Frank K. (Water resources research, 2018)
To test the hypothesis that wildfire smoke can cool summer river and stream water temperatures by attenuating solar radiation and air temperature, we analyzed data on summer wildfire smoke, solar radiation, air temperatures, precipitation, river discharge, and water temperatures in the lower Klamath River Basin in Northern California. Previous studies have focused on the effect of combustion heat on water temperatures during fires and the effect of riparian vegetation losses on postfire water temperatures, but we know of no studies of the effects of wildfire smoke on river or stream water temperatures. Wildfire smoke is difficult to quantify, but we successfully used a newly available daily high‐resolution (1 km) data set of aerosol optical thickness (AOT) derived from satellite imagery to represent smoke density during 6 years with extensive wildfire activity (2006, 2008, and 2012–2015). Smoke reduced solar radiation by 121 W m−2 per 1.0 AOT relative to clear‐sky conditions. Linear mixed‐effects models showed that on average, smoke cooled daily maximum and mean air temperatures by 0.98 °C and 0.47 °C per 1.0 AOT, respectively, across 19 remote automated weather stations. Smoke had a cooling effect on water temperatures at all 12 river and stream locations analyzed. On average, smoke cooled daily maximum and mean water temperatures by 1.32 °C and 0.74 °C per 1.0 AOT, respectively. This smoke‐induced cooling has the potential to benefit cold‐water adapted species, particularly because wildfires are more likely to occur during the warmest and driest years and seasons. Key Points Wildfire smoke cools river and stream water temperatures by reducing solar radiation and cooling air temperatures For both air and water, smoke has a greater cooling effect on daily maximum temperatures than daily mean temperatures This smoke‐induced cooling has the potential to benefit cold‐water adapted species in fire‐prone watersheds